The commemoration of the Reformation and the path to unity - Kelly, Gerard (The Australasian Catholic record, 2017)
The tumultuous events of the sixteenth century irrevocably changed the shape of the Western Church and thus Christianity more generally. The division that ensued affected not just the institutional life of the church, but also towns and villages, families and neighbours. For generations, people lived with the consequences of this division, often within the intimacy of their own family life. Fortunately, this has changed. The twentieth century is rightly referred to as the ecumenical century. We are able to point to milestones on the way to unity, beginning with the Edinburgh Missionary Conference in 1910, and then the First World Conference on Faith and Order in 1927, and the formation of the World Council of Churches in 1948. After the conclusion of the Second Vatican Council in 1965, the Catholic Church began to participate in ecumenical gatherings. Its entry brought a new way of ecumenical dialogue, and the era of the bilateral dialogue began, alongside the existing multilateral dialogue. Today the Catholic Church at the international level has been and/or continues to be in dialogue with the Anglican Communion, the Lutheran World Federation, the World Methodist Council, the World Alliance of Reformed Churches, the Baptist World Alliance, the Disciples of Christ (known in Australia as the Churches of Christ), Pentecostals, Evangelicals, and three families of Eastern and Oriental Orthodox Churches. In Australia the Catholic Church is currently engaged in dialogue with the Anglican Church, the Lutheran Church and the Uniting Church. The Catholic Church participates in a multilateral way through both the Joint Working Group with the World Council of Churches and as a member of the Faith and Order Commission of the World Council of Churches.